Topics, Skills, and Cases for an Undergraduate Musculoskeletal Curriculum in Southern Africa: A Consensus from Local and International Experts. (5th February 2020) - Held, Michael F.G.; Laubscher, Maritz; Graham, Simon M.; Kruger, Nicholas; Njisane, Phinda; Njisane, Vela; Dunn, Robert N.; Ngissah, Rueben K.S.; Lubega, Nicholas; Nortje, Mark; Dunn, Robert; Horn, Anria; et al.
Abstract : Background: Most patients with orthopaedic pathology in low to middle-income countries are treated by nonspecialists. A curriculum to prepare undergraduate medical students for this duty should reflect the local pathology and skills that are required to manage patients in a resource-restricted environment. The aim of this study was to establish and prioritize a list of core orthopaedic-related knowledge topics, clinical cases, and skills that are relevant to medical students in southern Africa and areas with a similar clinical context. Methods: A modified Delphi consensus study was conducted with 3 interactive iterative rounds of communication and prioritization of items by experts from Africa, Europe, and North America. Preferred priorities were selected but were limited to 50% of all of the possible items. Percent agreement of ≥75% was defined as consensus on each of these items. Results: Most of the 43 experts who participated were orthopaedic surgeons from 7 different countries in southern Africa, but 28% were general practitioners or doctors working in primary or secondary-level facilities. Experts prioritized cases such as patients with multiple injuries, a limping child, and orthopaedic emergencies. Prioritized skills were manipulation and immobilization of dislocations and fractures. The most important knowledge topics included orthopaedic infections, the treatment of common fractures and dislocations, any red flags alerting to specialist referral, and back pain. Surgical skills for the treatment of urgent care conditions were included by some experts who saw a specific need in their clinical practice, but these were ranked lower. Conclusions: A wide geographic, academic, and expertise-specific footprint of experts informed this international consensus through their various clinical and academic circumstances. Knowledge topics, skills, and cases concerning orthopaedic trauma and infection were prioritized by the highest percent agreement. Acute primary care for fractures and dislocations ranked high. Furthermore, the diagnosis and the treatment of conditions not requiring specialist referral were prioritized. This study can inform national curricula in southern Africa and assist in the allocation of student clinical rotations.